2014
DOI: 10.1016/j.jnucmat.2014.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical loading applied on the cladding tube during the pellet cladding mechanical interaction phase of a rapid reactivity initiated accident

Abstract: International audienceCalculations of the CABRI REP-Na5 pulse were performed with the ALCYONE code in order to determine the evolution of the thermomechanical loading applied on the cladding tube during the Pellet-Cladding Mechanical Interaction (PCMI) phase of a rapid Reactivity Initiated Accident (RIA) initiated at 280 °C that lasted 8.8 ms. The evolution of the following parameters are reported: the cladding temperature, heating rate, strain rate and loading biaxiality. The impact of these parameters on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the real reactor environment, the cladding tube is subjected to two orientation of mechanical loadings, i.e. along its axial and circumferential directions [132]. The mechanical behavior of the Cr coated Zr alloy cladding tubes under LOCA conditions is apparently affected by the stress state of the cladding tubes, which is determined by the formation of fission gases in the cladding tubes, the interaction between the fuel pellets and the cladding tubes, and the pressure of the coolant water outside the tubes [45].…”
Section: Mechanical Behaviormentioning
confidence: 99%
“…In the real reactor environment, the cladding tube is subjected to two orientation of mechanical loadings, i.e. along its axial and circumferential directions [132]. The mechanical behavior of the Cr coated Zr alloy cladding tubes under LOCA conditions is apparently affected by the stress state of the cladding tubes, which is determined by the formation of fission gases in the cladding tubes, the interaction between the fuel pellets and the cladding tubes, and the pressure of the coolant water outside the tubes [45].…”
Section: Mechanical Behaviormentioning
confidence: 99%
“…On the other hand, many more complex tests, generally carried out under irradiation, from which it is more difficult to obtain detailed measurements in situ, are performed continuously in different facilities [16]- [18], [24]- [27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The risk of cladding failure during in-reactor transient events may be increased, due to the embrittling effect of hydrogen. For instance, during a Reactivity Initiated Accident (RIA), caused by the ejection of a control rod assembly in PWRs, the cladding tube would be submitted at the beginning of the transient to a fast (strain rate of about 1 s −1 ) and biaxial mechanical loading (along cladding hoop and axial directions) due to Pellet-Clad Mechanical Interaction (PCMI) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…During this early stage of the transient, cladding temperature quickly increases (heating rate of the order of 10 4 • C.s −1 ) up to 600 • C on the tube inner surface while it remains around 350 • C on the outer surface [2]. Full-scale in-pile experiments performed in the NSRR or the CABRI reactors [4,5] have shown that, in the case of Zircaloy-4 cladding, the fuel rod can withstand a lower level of deposited energy during the RIA transient when it has a very high burnup, due in particular to hydrogen-induced cladding embrittlement.…”
Section: Introductionmentioning
confidence: 99%